2017
DOI: 10.11138/ccmbm/2017.14.2.247
|View full text |Cite
|
Sign up to set email alerts
|

Primary central nervous system germinal center B-like diffuse large B-cell lymphoma: a case report

Abstract: SummaryWe report a case of a 54-year-old HIV-negative female who presented with a 2-month history of ongoing post meridiem low-level fever and new onset progressive paralysis. On MRI (magnetic resonance imaging), an infiltrative enhancing lesion was noted, which initially resembled that of MS, but she reacted not sensitively with immunosuppressive therapy, we performed a brain biopsy to her, it turned out to be primary CNS (central nervous system) diffuse large B-cell lymphoma (DLBCL). And the morphology, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…In this regard, questions remain as to whether PVRL and PCNSL are synonymous or subtypes that could be further differentiated by their molecular signatures. While the ABC DLBCL subtype is widely recognized in both PCNSL and VRL (Camilleri-Broet et al, 2006 ; Bhagavathi et al, 2008 ; Cheng et al, 2008 ; Montesinos-Rongen et al, 2009 ; Hattab et al, 2010 ; Li et al, 2017 ; Belhouachi et al, 2020 ), many have independently reported the detection of GCB DLBCL in PCNSL and VRL (Bhagavathi and Wilson, 2008 ; Montesinos-Rongen et al, 2008 ; Wang, 2017 ; Arai et al, 2020 ), adding discordance to our current understanding. Admittedly, the classification of DLBCL based on gene expression profiling (Alizadeh et al, 2000 ) and IHC (Hans's algorithm) (Hans et al, 2004 ) was developed almost two decades ago; more importantly, they were not formulated to classify immune-privileged lymphomas such as PCNSL or VRL.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, questions remain as to whether PVRL and PCNSL are synonymous or subtypes that could be further differentiated by their molecular signatures. While the ABC DLBCL subtype is widely recognized in both PCNSL and VRL (Camilleri-Broet et al, 2006 ; Bhagavathi et al, 2008 ; Cheng et al, 2008 ; Montesinos-Rongen et al, 2009 ; Hattab et al, 2010 ; Li et al, 2017 ; Belhouachi et al, 2020 ), many have independently reported the detection of GCB DLBCL in PCNSL and VRL (Bhagavathi and Wilson, 2008 ; Montesinos-Rongen et al, 2008 ; Wang, 2017 ; Arai et al, 2020 ), adding discordance to our current understanding. Admittedly, the classification of DLBCL based on gene expression profiling (Alizadeh et al, 2000 ) and IHC (Hans's algorithm) (Hans et al, 2004 ) was developed almost two decades ago; more importantly, they were not formulated to classify immune-privileged lymphomas such as PCNSL or VRL.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, questions remain as to whether PVRL and PCNSL are synonymous or subtypes that could be further differentiated by their molecular signatures. While the ABC DLBCL subtype is widely recognized in both PCNSL and VRL (Camilleri-Broet et al, 2006;Cheng et al, 2008;Montesinos-Rongen et al, 2009;Hattab et al, 2010;Li et al, 2017;Belhouachi et al, 2020), many have independently reported the detection of GCB DLBCL in PCNSL and VRL (Bhagavathi and Wilson, 2008;Montesinos-Rongen et al, 2008;Wang, 2017;Arai et al, 2020), adding discordance to our current understanding. Admittedly, the classification of DLBCL based on gene expression profiling (Alizadeh et al, 2000) and IHC (Hans's algorithm) (Hans et al, 2004) was developed almost two decades ago; more importantly, they were not formulated to classify immune-privileged lymphomas such as PCNSL or VRL.…”
Section: Discussionmentioning
confidence: 96%